Cooperative Learning Model on Learning Outcomes in Basic Concrete Structure Subjects, Building Engineering Education Study Program, Faculty of Engineering, Makassar State University - Satriyati, Dewi; Pertiwi, Nurlita (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to evaluate the effectiveness of cooperative learning models in improving student learning outcomes in the Basic Concrete Structures course. This course, which is known to have a high level of difficulty, showed low learning achievements in the previous period. The results showed that the application of the cooperative learning model significantly improved student achievement, especially characterized by the percentage of A grades that increased dramatically in the 2024/2025 academic year. This finding indicates a positive correlation between the use of cooperative learning models and the improvement of student learning outcomes in the course.